THE INSCRIPTION OF COHORS III ALPINORUM FROM CECELA NEAR DRNIŠ (DALMATIA) AND THE QUESTION OF THE ROMAN MILITARY PRESENCE IN PETROVO POLJE DURING THE PRINCIPATE - Nikola Cesarik; Luka Drahotusky-Bruketa (Journal of Ancient History and Archaeology, 2020)
New insights about the previously unpublished inscription of cohors III Alpinorum, located in the Archaeological Museum in Zadar, are brought to light. Previously documented as an inscription from an unknown site, calling upon the diaries of a Friar Lujo Marun, it is now identified as an inscription from Petrovo polje; more precisely from the Cecela hilltop in the village of Siverić near the city of Drniš. So far, eight inscriptions with the record of Roman auxiliary units were found in the area of Petrovo polje, thus the inscription from Cecela should not be considered as an isolated case, but rather as a part of a relatively larger group of epigraphic records of Roman auxiliary units. The inscriptions were found in several locations (Tepljuh, Otavice, Kadina Glavica, Umljanovići) and as such, they represent the foundation of a hypothesis for the existence of several Roman auxiliary forts in Petrovo polje. On the other hand, it has recently been suggested that only one fort should be located in Petrovo polje, i.e. in the wider area of Kadina Glavica. The proposed location for the auxiliary fort is found at the slope below the place name "Glavičina" in the area of the village of Parčić near Kadina Glavica. From that point, several scholars are often mentioning ‘the auxiliary fort in Kadina Glavica’, sometimes even as a proven and undoubted fact. The authors hereby disregard such interpretation and give a new perspective on the presence of Roman soldiers in the area of Petrovo Polje.